2020
DOI: 10.1039/d0ra04370b
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ash deposition dynamic process in an industrial biomass CFB boiler burning high alkali and chlorine fuel

Abstract: Analysis of multiple deposits with different deposition times, piecing together the whole deposition process in 50 MW biomass CFB boiler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…6 However, gasification with lower-grade biomass such as agricultural residues may suffer from ash-induced problems related to slagging, fouling, and bed agglomeration. 7,8 Hence, a new understanding of the ash-induced problems arising from the gasification of agricultural residues in a DFB gasifier is crucial to allowing gasifiers to be designed for increased fuel flexibility and utilizing a wider range of feedstock other than woody biomass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, gasification with lower-grade biomass such as agricultural residues may suffer from ash-induced problems related to slagging, fouling, and bed agglomeration. 7,8 Hence, a new understanding of the ash-induced problems arising from the gasification of agricultural residues in a DFB gasifier is crucial to allowing gasifiers to be designed for increased fuel flexibility and utilizing a wider range of feedstock other than woody biomass.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of industrial-scale DFB gasifiers have been demonstrated using wood chips as the feedstock. There is a great need to improve fuel flexibility of DFB gasifiers because the cost of the feedstock has a significant impact on the economic performance of a gasifier . However, gasification with lower-grade biomass such as agricultural residues may suffer from ash-induced problems related to slagging, fouling, and bed agglomeration. , Hence, a new understanding of the ash-induced problems arising from the gasification of agricultural residues in a DFB gasifier is crucial to allowing gasifiers to be designed for increased fuel flexibility and utilizing a wider range of feedstock other than woody biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some agricultural residues have already been reported to exhibit challenging fuel properties for thermal conversion processes in DFB reactors. , This is because agricultural residues generally contain higher ash contents, especially potassium (K), which is of concern for fluidized beds as the high K retained in the bed will increase the propensity for agglomeration . A high level of gas-phase potassium in the flue and/or producer gases can also lead to fouling and corrosion of the heat exchange surfaces or downstream processes . The magnitude of each issue is closely associated with the transformation of K, combined with its interaction with the bed material, which varies depending on the chemical composition of each fuel.…”
Section: Introductionmentioning
confidence: 99%
“…9 A high level of gas-phase potassium in the flue and/or producer gases can also lead to fouling and corrosion of the heat exchange surfaces or downstream processes. 10 The magnitude of each issue is closely associated with the transformation of K, combined with its interaction with the bed material, which varies depending on the chemical composition of each fuel. More work is needed to better understand the aforementioned ash-induced problems in a DFB gasifier that may arise during gasification of agricultural residues.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in characteristics can cause problems during combustion, especially in plastic containing high alkali (K and Na) and chlorine content [3]. When the temperatures reach 600 o C, these species are discharged into the flue gas as HCl, KCl, K2SO4, and KOH, which can exacerbate the production of ash deposits and corrosion issues on the IOP Publishing doi:10.1088/1755-1315/1201/1/012001 2 heated metal surface [4]. The investigation conducted by Ma et al [5] Analyzed the deposits at the superheater and pre-protector Waste to Energy (WtE) plant and found abundant Cl, K, and Na content, which resulted in damage due to corrosion attack.…”
Section: Introductionmentioning
confidence: 99%